Finding Homologs in Amino Acid Sequences Using Network BLAST Searches. Issue 1 (13th February 2018) - Ladunga, Istvan
Abstract: BLAST, the Basic Local Alignment Search Tool, is used more frequently than any other biosequence database search program. We show how to run searches on the Web, and demonstrate how to increase performance by fine‐tuning arguments for a specific research project. We offer guidance for interpreting results, statistical significance and biological relevance issues, and suggest complementary analyses. This unit covers both protein‐to‐protein ( blastp ) searches and translated searches ( blastx, tblastn, tfastx) . blastx conceptually translates the query sequence and tblastn translates all nucleotide sequences in a database, while tblastx translates both the query and the database sequences into amino acid sequences. © 2017 by John Wiley & Sons, Inc.